Antidiabetic Activity of Various Leafy Extracts of Smilax zeylanica Linn in Streptozotocin Induced Diabetic Rats - Kumar Jena, Prabhat; Dinda, Subas Chandra; Ellaiah, P. (Asian Journal of Chemistry, 2012)
Smilax zeylanica Linn is found in the tribal area of Baipariguda (Dist: Koraput) Odisha, India and extensively used traditionally by the tribal people as anthelmintic, antibacterial, analgesic, impotency and antifungal agent. The present study involves the antidiabetic activity of different extracts of leaves of plant S. zeylanica using petroleum ether, ethyl acetate, n-butanol and ethanol as solvents. The various doses of solvents extracts were evaluated for their antidiabetic activity on Wister rat. All extracts exhibited the antidiabetic activity at 250 mg/kg concentration and the activities were well comparable with the standard drug, glibenclamide. Among all the solvent extracts, ethanolic extract showed better antidiabetic activity. The data were verified as statistically significant by using one way ANOVA at 5 % level of significance (p < 0.05).